2002
DOI: 10.1556/amicr.49.2002.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endotoxin level of healthy donors

Abstract: The plasma level of endotoxin was determined in 116 healthy blood donors. After a routine physical and laboratory investigations the endotoxin level was determined with Limulus amebocyte lysate assay (LAL-test) by the chromogenic kinetic method of Bio-Whittaker Co. (USA). Its sensitivity was 0.005-50 EU/ml. The plasma level of endotoxin in most of the healthy donors was less than 1 EU/ml (in the range of 0.01-1.0 EU/ml), but always measurable. The average +/- S.D. was 0.128 +/- 0.215 EU/ml. Because of the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 13 publications
6
33
0
Order By: Relevance
“…In that study it was shown that intragastrically applied 125 I-LPS, similarly prepared as the LPS in our present study, could be extracted in its entirety from the liver, thus showing that bioactive LPS is being absorbed from the gut and circulated through the body. Moreover, bioactive LPS is detectable in low amounts in the blood of healthy human subjects even in the apparent absence of infections (40,41), which would suggest that small amounts of LPS are being continuously absorbed from the gut, perhaps as part of a normal physiological process of yet unknown relevance.…”
Section: Discussionmentioning
confidence: 99%
“…In that study it was shown that intragastrically applied 125 I-LPS, similarly prepared as the LPS in our present study, could be extracted in its entirety from the liver, thus showing that bioactive LPS is being absorbed from the gut and circulated through the body. Moreover, bioactive LPS is detectable in low amounts in the blood of healthy human subjects even in the apparent absence of infections (40,41), which would suggest that small amounts of LPS are being continuously absorbed from the gut, perhaps as part of a normal physiological process of yet unknown relevance.…”
Section: Discussionmentioning
confidence: 99%
“…absorbed from the gut in healthy animals ( 12 ) and bioactived LPS is detectable in low amounts in the blood of healthy human subjects, even in the apparent absence of infections ( 21,22 ). Chylomicrons have been associated with metabolic endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…For recognition of the LPS molecular structure by the hosts, conserved ‘microorganism-associated molecular pattern'- or ‘pathogen-associated molecular pattern'-specific elements have been selected during evolution [35,36]. Derived from the gut Gram-negative bacteria, endotoxin continuously enters the blood in a ‘physiological manner' through the intestinal epithelial cells and the vessels of vena portae, resulting in measurable plasma levels in every healthy human subject, ranging from 0.01 to 1.0 endotoxin units/ml [37,38]. …”
Section: Bacterial Lps/bacterial Endotoxinmentioning
confidence: 99%